163 - DANCE AND CULTURE OF PEACE (Fiep Bulletin - online, 2011)
The planet for some time has been the stage for various scenes of violence. The twentieth century was marked by disputes and wars between countries, motivated by different interests. The violence at home, at work in the community among individuals and between countries leads to horrors, which directly and indirectly affect the daily lives of human beings. The biggest challenge is stopping the violence and all its forms. The search for peace has joined the staff of the companies and several. His promotion and maintenance became the mission of all. We need change, but real peace still seems far away. Some paths are being saved to the attainment of peace and the arts have a history of contribution to this. In this article, we attempt to relate the possibility of influence of dance as art, in building a culture of peace.
Keywords: dance; culture of peace; art